PENGEMBANGAN MEDIA VIDEO PADA MATERI TEKNIK DASAR BOLA BASKET SISWA SMK YAYASAN BUDI UTOMO LUBUKLINGGAU - Della Vya Ramadhona; M Rusni Eka Putra; Muhammad Suhdy (Jurnal Perspektif Pendidikan, 2022)
This study aims to develop instructional video media on the basic technical material of basketball and to determine the quality of the video in terms of validity and practicality. This research is a development research that refers to the development of the modified ADDIE model in 3 stages, namely Analysis, Design, and Development. The instruments used to measure the quality of the learning videos developed include validation sheets and practicality questionnaires. The product of this research is a video on the basic technical material of basketball for class X students of SMK Budi Utomo Foundation. The results showed that: (1) the LKS design seen from the aspect of validity was included in the very valid category of 81.3%., (2) the quality of the LKS viewed from the practical aspect was categorized as practical from the one to one test categorized as Very Practical and the small group with a percentage of 95 ,4% categorized as Very Practical